Institutional effectiveness of REDD+ MRV: Countries progress in implementing technical guidelines and good governance requirements - Ochieng, R.M.; Visseren-Hamakers, I.J.; Arts, Bas; Brockhaus, Maria; Herold, Martin (Elsevier, 2016)
The UNFCCC requires REDD+ countries wishing to receive results-based payments to measure, report and verify (MRV) REDD+ impacts; and outlines technical guidelines and good governance requirements for MRV. This article examines institutional effectiveness of REDD+ MRV by assessing countries' progress in implementing these technical guidelines and good governance requirements, from three dimensions. Ownership of technical methods examines whether countries own technical methods for forest area and area change measuring, and for estimating forest carbon stocks; and whether national MRV systems cover all forests, land uses and carbon pools. Administrative capacity examines development of administrative competence to implement MRV. Good governance examines whether countries espouses norms of good governance in their MRV systems. We apply these dimensions to assess and compare progress in 13 REDD+ countries, based on a review of national and international documents. Findings show that REDD+ countries have high to very high ownership of technical methods. However, majority ranks only low to moderate on administrative capacity and good governance. This means that although countries have started developing technical methods for MRV, they are yet to develop the competence necessary to administer MRV and to inculcate good governance in MRV. The article explain the scores and suggest ways of improving implementation of REDD+ MRV.